A responsabilidade criminal do compliance officer por crimes omissivos impróprios : a assunção da posição de garantidor através do contrato de trabalho - Braghirolli, Luiz Filipe de Andrade Neves (2022)
The present work deals with the criminal liability of the compliance officer through improper omissive crimes. The topic is extremely complex and involves a multidisciplinary approach that is characteristic of the compliance area. The tasks performed by the compliance officer within the business environment are extremely important for the prevention of crimes committed by the members of the organization. However, it is necessary to know whether there is a possibility of criminal liability of the compliance officer if he fails to fulfill his duty of vigilance over the source of danger. The monitoring, diagnosis and investigation of corporate risks are inherent to the profession, which is why they must be carried out by someone with mastery of the technique, as well as with factual capacity to act (resources - human and financial - sufficient, support from Senior Management, autonomy in exercise of functions, etc.). Finally, it is shown that the mastery of information by the compliance officer gives him an advantage when dealing with mastery over the source of danger, which is why the transfer of information to those who can intervene is extremely important.